TEACHING STRATEGIES IN STUDENTS’ MICRO TEACHING PERFORMANCE - Pipit Rahayu; Syamsiah Depalina Siregar (English Language Teaching and Research, 2018)
Microteaching is a teacher training technique in learning teaching skills. It employs real teaching situation for developing skills and helps to get deeper knowledge regarding the art of teaching with the significant reduction in the teaching complexities with respect to number of students in a class, scope of content, and timeframe, etc. Most of the pre-service teacher education programs widely use microteaching, and it is a proven method to attain gross improvement in the instructional experiences. Effective student teaching should be the prime quality of a teacher. The objective of this article is to analyze students’ teaching strategies used in micro teaching performances. The Population was English departments’ students from sixth semester class. Descriptive Qualitative is used in analyzed the data. Besides, the writer used observation checklist and video documentation of students’ micro teaching performance for collecting the data in gathering information on students’ teaching strategies. The writer found there were two types of teaching strategies used; direct instruction strategy and indirect instruction strategy. In direct instruction strategy, English students always used memory, cognitive and compensation strategies. Otherwise, metacognitive, affective and social strategies founds in terms of indirect strategy used by the students in micro teaching performance. Furthermore, the application of teaching strategies in teaching and learning process will help the teacher to convey information about teaching material to the students and to increase the learning outcomes. Keywords : Teaching Strategies, Micro Teaching Performance, direct instruction and indirect instruction strategies